Comparison of Hajj Financial Management in Malaysia and Indonesia - Ngah, Abdul Ghani Bin (Media Syari'ah, 2022)
The historical experience of organizing Hajj in Malaysia and Indonesia is long enough that the Malaysian Hajj Savings Institution (TH) and the Hajj Financial Management Agency (BPKH) were formed to manage the pilgrimage for the people of Malaysia and Indonesia. However, in practice, there are still many debates in terms of the use of contracts, Hajj management, facilities and human resources that have not been improved. This study aims to compare contract construction related to hajj performance which has an impact on haj financial management with a business and investment approach. This study uses a qualitative method using a document coding model. The data was obtained using a comparative normative approach, namely by exploring information about the contract, the impact of the contract on the financial management of the hajj in Malaysia and Indonesia. The results of this study can be concluded that the two countries use the Wakalah contract as the construction of the Hajj contract where the contract fulfills the pillars and conditions, but with a note that the other contract schemes still use the "Haj contract" at the beginning of the deposit or registration of the prospective Hajj and this should be considered by both governments. Also from the results of this study, Indonesia is far more complex in terms of concepts and mechanisms for haj financial management compared to Malaysia. Pengalaman sejarah pengelengaraan haji di Malaysia dan Indonesia cukup panjang sehingga tertubuhnya Lembaga Tabung Haji Malaysia (TH) dan Badan Pengelolaan Keuangan Haji (BPKH) untuk mengelola penyelengaraan haji bagi masyarakat Malaysia dan juga Indonesia. Namun, dalam pelaksanaannya, masih banyak perdebatan baik dari segi pengunaan akad, manajemen haji, fasilitas maupun sumber daya manusia yang belum ditingkatkan. Penelitian ini bertujuan untuk membandingkan konstruksi akad terkait kinerja haji yang berdampak pada pengelolaan keuangan haji dengan pendekatan bisnis dan investasi. Penelitian ini mengunakan metode kualitatif dengan menggunakan model pengkodean dokumen. Data yang diperoleh dengan menggunakan pendekatan normative komparatif yaitu dengan menggali informasi mengenai akad, dampak akad terhadap pengelolaan keuangan haji di Malaysia dan Indonesia. Hasil kajian ini dapat disimpulkan bahwa kedua negara menggunakan akad Wakalah sebagai konstruksi akad haji dimana akad tersebut memenuhi rukun dan syarat, namun dengan catatan skema akad yang lain masih digunakan “akad haji” di awal setoran atau pendaftaraan calon Haji dan ini seharusnya diperhatikan oleh kedua pemerintah. Dari hasil penelitian ini juga, Indonesia jauh lebih kompleks dari segi konsep dan mekanisme pengelolaan keuangan haji berbanding Malaysia.